Athletes' perceptions of the psychological, emotional, and performance effects of coaches' pre-game speeches - Vargas, T. M.; Short, S. E. (International Journal of Coaching Science, 2011)
Pre-game speeches are a popular coaching technique. While recent research has begun to examine their effectiveness (Vargas-Tonsing & Guan, 2007; Vargas-Tonsing & Bartholomew, 2006), little is known about athletes' perceptions of the effects of these speeches. Participants were 151 soccer players representing 10 elite soccer teams (five male and five female teams). Athletes had a mean age of 14.21 years (SD = 1.85) and reported an average of 8.83 years (SD = 2.26) of soccer playing experience. Athletes completed a questionnaire at the conclusion of a game that asked them to describe and elaborate on their perceptions of the coaches' pre-game speech; responses were analyzed qualitatively. The results showed that the majority of the athletes reported liking the speeches and indicated that the speeches impacted their performance and met their psychological, emotional and performance needs. The results offer insight into athletes' preferences for speech content and demonstrate the need for further research in this area.